2021
DOI: 10.3389/fmars.2021.752231
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Long-Term, Wide-Band and Deep-Water Soundscape Off Hawai’i

Abstract: Many animals use sound for communication, navigation, and foraging, particularly in deep water or at night when light is limited, so describing the soundscape is essential for understanding, protecting, and managing these species and their environments. The nearshore deep-water acoustic environment off the coast of Kona, Hawai’i, is not well documented but is expected to be strongly influenced by anthropogenic activities such as fishing, tourism, and other vessel activity. To characterize the deep-water sounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 67 publications
1
3
0
Order By: Relevance
“…In this study, we observed the opposite trend at the Hawaiʻi site which had higher sound levels corresponding with humpback whale chorusing which likely reflects the variability in animal presence across islands annually. More recent long-term, broadband soundscape work off Kona, Hawaiʻi revealed more subtle seasonal trends in the deep-water soundscape, with sound levels within the Hawaiʻi range reported in this study but exhibited low frequency seasonality in the winter driven by humpback whales (Merkens et al, 2021). With the inclusion of consecutive years of data, this study expands on the comprehensive Hawaiian Archipelago wide soundscape analyses conducted in Lammers et al (2023a) within the sanctuary and monument.…”
Section: Soundscape Comparisons and Challengessupporting
confidence: 64%
See 2 more Smart Citations
“…In this study, we observed the opposite trend at the Hawaiʻi site which had higher sound levels corresponding with humpback whale chorusing which likely reflects the variability in animal presence across islands annually. More recent long-term, broadband soundscape work off Kona, Hawaiʻi revealed more subtle seasonal trends in the deep-water soundscape, with sound levels within the Hawaiʻi range reported in this study but exhibited low frequency seasonality in the winter driven by humpback whales (Merkens et al, 2021). With the inclusion of consecutive years of data, this study expands on the comprehensive Hawaiian Archipelago wide soundscape analyses conducted in Lammers et al (2023a) within the sanctuary and monument.…”
Section: Soundscape Comparisons and Challengessupporting
confidence: 64%
“…This study shows the presence of inter and intra-island variations in the soundscape of HIHWNMS, which fluctuate annually due primarily to changes of biological sources (Kaplan et al, 2018;Kügler et al, 2020;Merkens et al, 2021). In temperate and tropical waters with relatively shallow reef environments, biological sources are often the primary drivers of temporal sound level fluctuations (e.g.…”
Section: Hihwnms Soundscape Driven By Biological Sourcesmentioning
confidence: 85%
See 1 more Smart Citation
“…An additional ‘junk’ class containing clusters of detections from noise sources such as ships and echosounders was included to prevent misclassifications of these sources as odontocetes. These noise sources were picked up by the detector due to their commonality in the data, particularly at the Kona site [ 44 ], and the similarity of these signals to echolocation clicks. Clusters of sperm whale, Physeter macrocephalus , echolocation clicks were also grouped into this ‘junk’ class due to the difficulty of separating these clicks from high-frequency ship noise as both can occupy the same frequency range between ~5–20 kHz.…”
Section: Methodsmentioning
confidence: 99%